Weak and Strong Points in The Perception of Own Preparedness of Prospective Math Teachers - DOFKOVÁ Radka; CHUDÝ Štefan (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
Research projects in the area of testing the quality of perception of own preparedness of prospective math teachers are taking place in many countries, however, a generally applicable instrument for its testing has not been found. The main goal of this article is to explicitly define the determinants influencing prospective math teachers' preparedness to teach math so that it is possible to use these areas to create a new research tool. Due to the large number of items the Mathematics Teaching Self-Efficacy Scale (Ryang 2010) was used among 121 students of the math teaching program at the Teacher Education Faculty in Olomouc. Based on the results of factor analysis areas of weak and strong points of prospective teachers' preparedness were identified. In order to get a more compact idea statistically significant difference in the respondents' answers was assessed based on their respective study groups. The results proved to be largely consistent.